Symptomatic intra-articular ganglion cyst of the knee - Che Ahmad, Aminudin; Osman Cassim, Samsudin; Mohd Yusof , Hyzan; A.H, Hamzaini; Mohammad, Zahiah (Malaysian Medical Associations, 2004)
We are reporting a case of a patient with a symptomatic intra-articular ganglion of the knee arising from infrapatellar fat pad. Plain radiograph and Magnetic Resonance (MR) images were correlated with arthroscopic examination and histological findings. The cyst was removed and post operatively patient regained full extension.